Giska Store Laundry Soap Product Brand Selection using Analytical Hierarch Process Method Guidelines for Author - Putri Ulil Fatma Aulia; Sudin Saepudin; Falentino Sembiring (Jurnal Mantik, 2022)
Soap is a material for cleaning clothes is a basic requirement because every day people use soap for all needs. So many products of laundry soap brands that compete with each other in the market both local and foreign products. The importance of Decision Support System to assist buyers of laundry soap brand products in determining the choice of product brands that suit their needs and criteria. Analytical Hierarchy Process (AHP) is a multi-criterion decision-making method that can help certain parties in making the best decisions to achieve maximum results. Priority the most important criteria in determining the selection of brands of laundry soap products where the price of quality and capacity becomes the priority of users in the selection of brands of laundry soap products and the highest matrix value.